From evaluation to reflection-on-action: Lessons learnt from the impact of a distance education programme - Aluko, Ruth (South African Journal of Higher Education, 2016)
Reflection-on-action is necessary to derive meaning from one’s experiences. This paper revisits research data from an elongated study on the impact of a distance education programme on the professional practice of graduates. The study focused on 300 graduates and 128 principals, selected through multi-stage and purposive sampling. The researcher used a mixed-methods research design with specific focus on Kirkpatrick’s, and Baldwin and Ford’s training evaluation models. The researcher’s curiosity was triggered by the need to understand possible reasons for the participants’ views, as these are contrary to the norm. This account indicates a clear institutional policy on quality assurance, practices guided by the policy, an ongoing monitoring of the distance education students’ profiles, improved programme design, student support structures, programme design and research focused on programmes as possible reasons. The author argues that higher education practitioners, irrespective of delivery mode, could benefit from the valuable lessons learnt from the exercise.